Relationship Of Organizational Culture With Employees Performance At The Langsa Lama Puskesmas kab. Aceh Timur in 2021 - Amsarah Br.Munthe (Jurnal EduHealth, 2022)
Background: Employee performance is Employee Performance (Employee) Employee performance is a work achieved by an employee in carrying out the tasks assigned to him based on skills, experience, and sincerity and time. One of the causes of employee performance is based on the results of an initial survey conducted by researchers on 8 employees at the Langsa Lama Health Center, Kab. East Aceh found that they lack discipline in using their working time, such as during working hours sometimes employees are not at work because they are returning home. Performance is the result of work in quality and quantity achieved by a person in carrying out his functions in accordance with the responsibilities given to him. Methods: the research method used is Spearman's Rho design. Results : The results showed that the organizational culture is very good (51.3%), and employee performance is very good (50.0%). Based on the results of the Spearman's Rho statistical test, a p-value of 0.031 (p<0.05) was obtained, it was concluded that the better the performance of the employees at the Puskesmas, the better the organizational culture at the Langsa Lama Health Center. and vice versa, the performance of the employees at the health center is sufficient and the organizational culture is lacking. Discussion: It is hoped that employees can perform their duties well, be responsible and disciplined so that employees arrive on time at the health center and become responsible health employees with a disciplined attitude not to go home at an inconvenient time determined by the puskesmas. and very good employee performance (50.0%). Based on the results of the Spearman's Rho statistical test, a p-value of 0.031 (p<0.05) was obtained, it was concluded that the better the performance of the employees at the Puskesmas, the better the organizational culture at the Langsa Lama Health Center. and vice versa, the performance of the employees at the health center is sufficient and the organizational culture is lacking. Discussion: It is hoped that employees can perform their duties well, be responsible and disciplined so that employees arrive on time at the health center and become responsible health employees with a disciplined attitude not to go home at an inconvenient time determined by the puskesmas. and very good employee performance (50.0%). Based on the results of the Spearman's Rho statistical test, a p-value of 0.031 (p<0.05) was obtained, it was concluded that the better the performance of the employees at the Puskesmas, the better the organizational culture at the Langsa Lama Health Center. and vice versa, the performance of the employees at the health centers is sufficient and the organizational culture is lacking. Discussion: It is expected that employees can do their jobs well, be responsible and disciplined so that employees arrive on time at the health center and become responsible health employees with a disciplined attitude not to go home at an inconvenient time determined by the puskesmas. 031 (p<0.05), it can be concluded that the better the performance of the employees at the Puskesmas, the better the organizational culture at the Langsa Lama Health Center. and vice versa, the performance of the employees at the health center is sufficient and the organizational culture is lacking. Discussion: It is hoped that employees can perform their duties well, be responsible and disciplined so that employees arrive on time at the health center and become responsible health employees with a disciplined attitude not to go home at an inconvenient time determined by the puskesmas. 031 (p<0.05), it can be concluded that the better the performance of the employees at the Puskesmas, the better the organizational culture at the Langsa Lama Health Center. and vice versa, the performance of the employees at the health center is sufficient and the organizational culture is lacking. Discussion: It is hoped that employees can perform their duties well, be responsible and disciplined so that employees arrive on time at the health center and become responsible health employees with a disciplined attitude not to go home at an inconvenient time determined by the puskesmas.